KARAKTERISTIK PETANI DI KABUPATEN KARANGANYAR, PROVINSI JAWA TENGAH - Sukadi, Sukadi (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2016)
The purpose of research is to describe the characteristics of farmers in Karanganyar district. Research done in the characteristics of farmers in Karanganyar, Central Java Province. The timing of the study lasted for one month in September 2014. The population in this study is the farmers who are members of farmer groups. The sampling technique was conducted with a random group of many stages (multistage cluster random sampling), Data Collection Techniques of this study are primary data and secondary data. Data analysis technique is descriptive analysis techniques. The results were obtained Characteristics Farmers in Karanganyar as follows: Farmers mostly aged between 46-65 years of as much as 54.21%, the majority of farmers Education Elementary and junior high school education is 31.78% and 31.78% elementary and junior high school education, Farmers has never participated in a training activity / non-formal education (in the past year) as much as 32.71% of the farmers, farmers income mostly less than Rp5.000.000,- / season as much as 53.27%, tenure farmers much less than 5,000 m2 69.16%, Tier of cosmopolitan weak farmer is as much as 43.93%, Old farming is an average of 10-20 years of as much as 43.93%, age of farmer group membership is average of less than 10 years as much as 59.88%.